Young Offenders on Community Orders : Health, Welfare and Criminogenic Needs. - Kenny, Diana T.; Nelson, Paul K. (Sydney : Sydney University Press, 2008)
Offending behaviour in childhood is a significant predictor of subsequent offending; early intervention is more effective than that provided later. This research aimed to advance understanding of juvenile crime, its health/substance abuse patterns, cognitive correlates and offence trajectories to facilitate effective policies and reduce recidivism.
7.5 Childhood Trauma Questionnaire (CTQ) -- 7.6 CTQ, Conduct Disorder and Substance Abuse Disorder -- 7.7 Self-report of mental health -- 7.8 Suicide and Self-harm (SSH) -- 7.9 Relationships: Peers and other sources of emotional support -- 7.10 Bullying -- 7.11 Gambling -- 7.12 Life satisfaction -- 7.13 Life concerns -- 7.14 Summary and conclusions -- 7.15 References -- Chapter 8: Alcohol, Tobacco and Other Drug Use -- 8.1 Alcohol use -- 8.2 Tobacco use -- 8.3 Substance use -- 8.4 Drug treatment -- 8.5 Summary and conclusions -- 8.6 References -- Appendix 1 -- Physical health assessment
Description based upon print version of record.
Physical health questionnaire
JSTOR
Keywords: Juvenile delinquents -- Health and hygiene -- Australia -- New South Wales -- Statistics; Health surveys -- Australia -- New South Wales; Youth -- Government policy -- Australia -- New South Wales; Health behavior in adolescence -- Australia -- New South Wales; Jeunes délinquants -- Santé et hygiène -- Australie -- Nouvelle-Galles du Sud -- Statistiques; Jeunesse -- Politique gouvernementale -- Australie -- Nouvelle-Galles du Sud; Habitudes sanitaires chez l'adolescent -- Australie -- Nouvelle-Galles du Sud; Health behavior in adolescence; Health surveys; Juvenile delinquents -- Health and hygiene; Youth -- Government policy; New South Wales; Electronic books; Statistics